The Effect of Taxpayer Awareness, Fiskus Services and Sanctions Taxation on Corporate Taxpayer Compliance - R. Rahmi (Golden Ratio of Taxation Studies, 2021)
In 2011-2013, there was a decrease in the level of corporate taxpayer compliance at KPP Pratama Makassar South. This study aims to test empirically and analyze the influence of taxpayer awareness, tax authorities, and tax sanctions against corporate taxpayer compliance at the Primary Tax Service Office South Makassar. This research was conducted using a survey method of corporate taxpayers at KPP Pratama South Makassar. Samples were obtained by random sampling . Data collection methods through questionnaires, and next data analyzed use analysis regression linear double. Results study this is Awareness must tax, service officer tax/tax and penalty taxation in a manner simultaneous no influential positive and significant on corporate taxpayer compliance. Variable Service of tax officers/tax authorities and tax sanctions partially influential positive but no significant to performance obedience must tax body. Awareness must tax in a manner Partial no influential significant in a manner partial to mandatory compliance tax body.